Impactos sobre a biota e a qualidade de latossolos cultivados com cana-de-açúcar, em Quirinópolis, Goiás - Sant'Ana, Georgia Ribeiro Silveira de (2014)
The expansion of the culture of sugar cane in Brazil is being driven towrds the Brazilian Midwest, particularly in the states of Mato Grosso do Sul (MS) and Goiás, since the end of last century. Goiás stands out in this process, but is now among the three states with the largest cultivated area and production. South mesoregion excels, especially micro-Quirinopolis (MRQ), where the process began in 2004, replacing grain areas and pastures. This research aims to analyze the influence of different management practice in the cultivation of cane sugar in the MRQ, using sensitive biological and physico-chemical indicators of water quality and soil, to contribute to sustainable models with parameters that sugarcane expansion. Eight sampling sites were selected in areas occupied by soil type Red Oxisol dystrophyc and distroferric, with previous uses of soybeans, pasture and pasture / soybean, and in parallel, two profiles as a reference, with native vegetation, the type Semidecidual Forest, once dominant. Were also selected two stocks next crop of sugar cane, collections with the Montate and downstream of each channel. Descriptions and Samples of soil and water were carried out in September 2010 and March 2011. Proceeded physical, chemical and biological analysis of soil and water by applying methods of Pedology, Biology and Ecology. It was concluded that different agricultural practices directly influence the dynamics of soil and water, unbalancing the biota, due to change in their physico-chemical and biological attributes that succession soy / sugar use biomarkers showed. The same applies to the water, but these can not yet be regarded as polluted by CONAMA parameters.